PENGARUH PENGGUNAAN MEDIA BIG BOOK TERHADAP KEMAMPUAN MEMBACA SISWA KELAS 1 SD NEGERI KEDUNGTURI KECAMATAN TAMAN SIDOARJO - Nilam Ismi Saraswati; Erlin Kartikasari; Novina Desiningrum (Bajang Institute, 2023)
This research is entitled The Effect of Using Big Book Media on Reading Ability of Grade 1 Students of Kedungturi Public Elementary School, Taman Sidoartjo District. This study aims to find out the application of Media Big Book in reading skills possessed by first grade students at Kedungturi Public Elementary School, Taman District, Sidoarjo. The research method used is quantitative research with the type of experimental research method applied to a research where it is used to explore the effects caused by one treatment on another under controlled conditions. The research design in this study was a pre-test (initial test) and post-test (final test) in which the population and sample in this study were all class I students with a total of 52 students from class IA with 26 students in class IB with a total of 26 students. Kedungturi Public Elementary School Media Big Book has a significant effect on the learning outcomes obtained by first grade students at Kedungturi Publik Elementary School, Taman Sidoarjo District. This is evidenced by the results of the Paired Sample T-test obtained, namely the significance value (2tailed) shows the number 0.000 <0.05 and the T-test result is 7.756 meaning that there is a significant influence on the use of Big Book media. The influence of Big Book Media on first grade students at Kedungturi Public Elementary School, Taman Sidoarjo District shows the number 11.53. Based on the acquisition of these values stated that there was an influence on the experimental class